Public expenditure, economic growth and poverty alleviation. Issue 6 (13th June 2016) - Sasmal, Ritwik; Sasmal, Joydeb
Abstract : Purpose: – The purpose of this paper is to examine the impact of public expenditure on economic growth and poverty alleviation in developing countries like India. If poverty and inequality are high, the government may resort to distributive policies at the cost of long-term growth. The distributive policies and poverty alleviation measures fail to achieve success due to lack of good governance, lack of proper targeting and problems in the implementation of such schemes. On the other hand, if the nature of public expenditure is such that it enhances per capita income, it will help reduce poverty. Design/methodology/approach: – After analytical digression and construction of hypotheses panel regression has been done using state-level data in the Indian context to empirically verify the above propositions. Both Fixed effects and Random effects models have been used for this purpose. Findings: – The results show that in states where ratio of public expenditure on the development of infrastructure such as road, irrigation, power, transport and communication is higher, per capita income is also higher and incidence of poverty is lower indicating that economic growth is important for poverty alleviation and development of infrastructure is necessary for growth. Originality/value: – This study demonstrates how public policy and public finance can be used as instruments for removal of poverty.